Особливості сценарно-цільового підходу до аналізу об’єктів дієвої аналітики - Koval, O. V.; Boyko, Yu. D.; Volkova, K. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
Actionable Analytics is one of ten trends in information technology today. Key elements of actionable analytics are purposefulness and information analysis scenarios. Realization of information analysis scenarios mandates the development of a general tool for describing the different forms of analytical information system elements interactions. Such a tool provides an implementation of actionable analytics. The usage of the scenario-goal approach to actionable analytics objects analysis gives the possibility to develop such a tool. According to the scenario-goal approach to actionable analytics objects analysis, the process of the information analytical system development is considered as the sequence of building its models. At the first stage, a conceptual model of the information analytical system is built by using a scenario-goal approach. This model describes general notions of functional and information components: the goal, scenario, meta description, and knowledge. The construction of a conceptual model is illustrated using an analysis of key factors of improving the quality of life in the region as an example.